Proposed interior design scheme of Number Eight Guesthouse for S-A Two Sdn. Bhd. at Lot 1, Jalan Sultan Azlan Shah 31400 Ipoh, Perak Darul Ridzuan / Muhd Shahreen Houd - Houd, Muhd Shahreen (Faculty of Architecture, Planning and Surveying, 2011)
This project is about Proposed Interior Design Scheme of Number Eight Guesthouse for S-A Two Sdn Bhd at Lot 1, Jalan Sultan Azlan Shah 31400 Ipoh, Perak Darul Ridzuan. Number Eight Guesthouse was well known as a Budget Hotel since opened in 2005. The client of this project is S-A Two Development Sdn. Bhd which is the company is a hotel development company. The reason to proposed this project is because the client decided to widen its business outside Kuala Lumpur, preferably those of tourist attraction cities especially ones with tradition heritage like Ipoh, Perak. For this proposed project site at Ipoh, Perak was choose after had done survey in few place and it seems that the site choose gives good impact and the surroundings suit the business purpose. The objective is to create a very well Budget Hotel with comfort and style with a good price related to the area has been chosen. This proposed interior design scheme for Number Eight Guesthouse is to attract more customers either from Malaysia and the tourist came to Ipoh since Malaysia Government wants to enhance tourism sector than previous year. The target market for the customers of this hotel is the tourist who needed and interest a accommodation with a low price, comfort and style.